2020
DOI: 10.3390/safety6040057
|View full text |Cite
|
Sign up to set email alerts
|

Teenage and Adult Drivers’ Views of a One-Day Car Control Class on a Closed-Road Course

Abstract: Traffic-related crashes impact drivers of all ages. Post-license driving classes have emerged to equip drivers with higher level skills needed to prevent and avoid emergency situations. A performance driving center offers teenage and adult car control classes designed to address defensive driving skills through both classroom instruction and hands-on practice on a closed-road track. To obtain the views from teenagers and adults, both groups completed a survey immediately after their classes, and the adults com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…The results from the previous study [21], suggested that both teen and adult drivers considered the information about ABS and the experience activating ABS to be of high importance, which supports the hypothesis that many drivers did not have prior knowledge or experience with ABS. This is consistent with the observations from Mazzae, Garrott & Snyder [6], that drivers did not understand the purpose of ABS.…”
Section: Performance Driving Center Classessupporting
confidence: 55%
See 4 more Smart Citations
“…The results from the previous study [21], suggested that both teen and adult drivers considered the information about ABS and the experience activating ABS to be of high importance, which supports the hypothesis that many drivers did not have prior knowledge or experience with ABS. This is consistent with the observations from Mazzae, Garrott & Snyder [6], that drivers did not understand the purpose of ABS.…”
Section: Performance Driving Center Classessupporting
confidence: 55%
“…Once the first group of drivers completes the exercise, the drivers and passengers switch seating positions, and the exercise is repeated. A previous study investigated the drivers' views of the class, where a pre and posttest survey was conducted with several one-day teen and adult classes [21]. The results suggested that both the teens (N = 80) and adults (N = 177) identified ABS braking as one Drivers slowly drive through the course and are instructed to brake at a designated set of cones and come to a complete stop before receiving feedback from the instructor.…”
Section: Performance Driving Center Classesmentioning
confidence: 99%
See 3 more Smart Citations